SOCIALIZATION ACTIVITIES ABOUT IMMIGRATION AND IMMIGRATION POLYTECHNIC BY IMMIGRATION POLYTECHNIC CADETS AT SMAN 5 MALANG - Aldi Raihan Zahy; Koesmoyo Ponco Aji (Polteknik Imigrasi, 2021)
Dissemination of Immigration and Immigration Polytechnic at SMAN 5 Malang by Immigration Polytechnic Cadet aims to disseminate immigration informations and also introduce Immigration Polytechnic to the wider community. In this activity, the cadets also took the time to participate in joint gymnastics which aims to increase immunity during the covid-19 pandemic. The implementation of this socialization is one of a series of internship activities for the Immigration Polytechnic Cadets in the Malang City area. This is a service to the community in order to provide immigration information for the wider community. This activity was carried out by the Immigration Polytechnic cadets in their respective areas due to the covid-19 pandemic where the cadets had to learn from their respective homes and participate in online learning activities. With this socialization, the public especially the students of SMAN 5 Malang are expected to know and understand about Indonesian immigration and about the Immigration Polytechnic.